Endoscopic ultrasound‐guided fine needle aspiration with contrast‐enhanced harmonic imaging for diagnosis of gallbladder tumor (with video). (10th November 2020) - Tamura, Takashi; Yamashita, Yasunobu; Kawaji, Yuki; Hatamaru, Keiichi; Itonaga, Masahiro; Ashida, Reiko; Okada, Ken‐ichi; Kawai, Manabu; Yamaue, Hiroki; Kitano, Masayuki
Abstract : Highlight Endoscopic ultrasound‐guided fine needle aspiration with contrast‐enhanced harmonic imaging is useful for accurately and safely obtaining tissue from a gallbladder tumor. Tamura and colleagues demonstrate how contrast‐enhanced harmonic endoscopic ultrasound facilitates puncturing the gallbladder tumor while avoiding fluid spaces as it demarcates the borderline between the tumor and fluid spaces.